Effective Financing of Environmentally Adjusted Multifactor Productivity Growth in Sustainable Development Framework – An International Comparative Study - Prokop, Viktor; Stejskal, Jan; Kuba, Ondrej (European Journal of Sustainable Development, 2019)
Sustainability in innovation activities financing is undoubtedly one of the important requirements that determine the business environment in all developed countries of the world. Different countries apply different innovation models or policies, ways to support or finance their entrepreneurial innovation activities respectively. They significantly shape or cultivate an innovative environment in which different relationships and linkages between actors take place. Therefore, it is necessary to analyze individual determinants, their sustainability, and their efficiency in view of the expected outcomes – environmentally adjusted multifactor productivity growth. We used data from the OECD statistics 2009-2013 for all developed countries in the world. We used DEA (data envelopment analysis) and super-efficiency-DEA method for our international comparative study. Our results show that the developed countries use the combination of private and public financial sources in different way. These are countries that can be perceived as a benchmark - it is therefore possible to compare even partial values of indicators and define public policies for support of selected entrepreneurs. The DEA software also allows you to obtain a numerical benchmark of inputs and outputs for every country. Our finding contributes to the theoretical debate on innovation and eco-innovation models in framework of sustainable development. The results of the analysis confirm the importance of financial sources, human resources and sustainable public sector interventions that influence the environmentally adjusted productivity growth. Keywords: environmentally adjusted productivity growth, sustainable development, financing, OECD